Fuktkvotens inverkan på oljeupptag och pigmentinträngning i tall (Pinus sylvestris L.) och gran (Picea abies L. Karst) vid impregnering med Linotechmetoden - Sjöström, Anna (SLU/Dept. of Forest Ecology and Management, 2008)
Wood has always been an important material for people, and it is used for many applications. As for example, fuel for cooking and heating houses, construction materials and for constructing means of transport. Since wood also is a material that with time biologically degrades due to activity by micro organisms and wood fungi it is important to find ways to protect and further lengthen the life span of the material when in service. One method is to decrease the amount of water in the material by impregnation with an hydrophobic oil. The Linotech method which uses only pure linseed oil is one such possible method. The aim of this study was to investigate the possibility to at the same time impregnate and stain/colour wood samples of pine and spruce by using the Linotech method. In this study one pigment (carbon) dissolved in mineral oil and one colouring agent dissolved in an organic solution was mixed into the linseed oil before the impregnation. The level of uptake for oil and colour was examined and evaluated. Furthermore it was analysed however the initial moisture content influence the results. The water repellence in the wood samples was also tested with a drip test. In this study was a total of 40 wood samples with the dimensions 500x50x25 mm used, 20 from pine and spruce respectively. All samples were made of two trees harvested in a coniferous forest in northern Sweden at Vindeln Experimental Forests (64°10'N, 19°46'E, 160 meters above sea level). The site index in the stand was 4.1 m3ha-1year-1. The initial moisture content was determined for all the samples. Then half of them were dried and their moisture content was calculated again according to the dry weight method. Thereafter all the samples were impregnated with the Linotech method. The treatment consisted of two different parts, 50 minutes of pressure (12 MPa) and 50 minutes of warmth (70-90°C). No vacuum was drawn due to a central power break in Vindeln. Finally, the wood samples were sawn into smaller pieces. The samples of pine were sawn at 1, ...